Recovery and Resignification of Religious Iconography in Francisco de Goya’s Desastres de la guerra (Disasters of War) Series - Romero Cerna, Derli; Vidaurre Arenas, Carmen V. (Eikón / Imago, 2024)
In the present article, we compare some of Goya’s etchings with images from religious art that were available during the artist’s lifetime to delineate the similarities existing between them, concerning the positions and postures of its main subjects. We describe the iconography of a selection of prints in order to find details that in some cases suggest the close relationships and, in others, the common styles existing in Goya’s artwork. The methodology is centered on the statements of studies in three stages of Erwin Panofsky, with this we refer to pre-iconographic, iconographic, and iconological. This analysis considers elements that guard possible association on interpretative grounds according to the historic-social context of the artwork production. The recovery of particular elements of religious iconography it’s not always carried from one perspective but from various viewpoints.